A CONVENIENT SYNTHESIS OF [RU(ETA-C5H5)(PPH3)(CO)CL] AND THE CATIONS [RU(ETA-C5H5)(PPH3)L(CO)]+ [L = CO, PME3, OR P(OPH)3] - Davies, S; Simpson, S (1984)
Treatment of [Ru(η-C5H5)(PPh3)2Cl] with sulphur under carbon monoxide at 1-3 atm in hot toluene gives quantitative yields of [Ru(η-C5H5)(PPh3)(CO)Cl], which can be further treated in warm methanol with CO, PMe3, and P(OPh)3 to give the cations [Ru(ηC5H5)(PPh3)(CO)2] +, [Ru(η-C5H5)(PPh3)(PMe 3)(CO)]+, and [Ru(η-C5H5)(PPh3){P(OPh) 3}(CO)]+ respectively.